Comprehensive Review of the Effects of Treated Vermicompost on Soil Health, Plant Growth, and Yield of Okra (Abelmoschus esculentus L.) - Anil, Nabam; Gumde, Nabam; Bibi, Iqra; Bairwa, Rajendra (Indus Journal of Bioscience Research, 2025)
Vermicomposting is an environmentally sustainable method for restoring soil health, promoting plant development, and augmenting agricultural production. This study emphasizes its contribution to increasing okra (Abelmoschus esculentus L.) output by augmenting soil with vital nutrients (N, P, K) and fostering microbial activity, hence improving soil structure, water retention, and plant resistance. Research indicates that the use of vermicompost with NPK fertilizers markedly enhances okra growth, fruit output, and soil organic matter, while decreasing nutrient leaching. Moreover, vermicompost inhibits soil-borne pathogens, promotes root growth, and fosters sustained soil fertility. Notwithstanding its benefits, obstacles like nutritional fluctuation, protracted processing duration, and restricted farmer adoption remain. Advancements in vermiculture, microbial inoculants, and biofortified formulations provide ways to enhance its efficiency. Case studies demonstrate that vermicompost is an effective substitute for synthetic fertilizers, fostering sustainable agriculture and environmental preservation.